Fundamental Movement Skills (Fms) Learning Model for Primary School - Ningrum, Desy Tya Maya; Mahyudi, Yafi Velyan; Arisman, Arisman (Halaman Olahraga Nusantara : Jurnal Ilmu Keolahragaan, 2024)
Learning fundamental skills movements can be done with a game approach and using simple tools. This study aims to develop a game-based basic motion learning model in elementary schools, and to see the effectiveness of the developed model. The subjects in this study amounted to 158 consisting of 5 elementary schools, experimental and control subjects were taken from a sample of 68 students. The research method used is Research and Development from Borg and Gall. Based on the results of the validation of physical education learning experts, movement learning experts and game experts declared valid for trials with locomotors obtaining percentages of 80.00% and 85.00%, non-locomotor basic movements obtained percentages of 80.26% and 82.89% and in The manipulative basic movement learning model obtained a percentage of 80.88% and 84.38%, respectively. The results of the small group trial state that the learning model developed can be implemented by students with a percentage of 79.79% and the large group at gets a percentage of 82.14%,. The results of the effectiveness state that the developed model can improve the basic movement skills of walking, running, throwing, catching and jumping with a mean difference of t0 is 15,462 > t-table 1,668, degrees of freedom 66 = 0.05. The conclusion is that the developed model is valid and can be applied to physical education learning, and can improve the basic movement skills of elementary school students.